Analisis Pelaksanaan Prinsip-Prinsip Good Governance dalam Penyusunan Rencana Kerja Pemerintah Desa Tahun 2026 (Studi di Desa Pusar, Kecamatan Baturaja Barat, Kabupaten Ogan Komering Ulu) - Jepriawan, Deni; Yahnu Wiguno Sanyoto; Eva Susanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The preparation of the Village Government Work Plan (RKPDes) is an essential instrument in village development planning, serving as the primary reference for village programs within a one-year fiscal period. The preparation process is not merely administrative but also reflects the quality of village governance. This study aims to analyze how the principles of good governance are implemented in each stage of the RKPDes preparation, including village deliberations, the drafting process, and the finalization of the RKPDes. Accordingly, this research is expected to provide an empirical overview of the quality of village governance within the development planning process. The findings show that the implementation of good governance principles in Pusar Village has begun to take shape but has not yet been optimal. Transparency still needs improvement, particularly in the equitable dissemination of information to the community. Community participation is relatively good during the village deliberation stage but remains limited during the drafting and finalization stages. Government accountability demonstrates progress, although documentation challenges persist. Meanwhile, the effectiveness of planning is considered sufficient in accommodating priority needs, although it remains influenced by budget constraints. This study is expected to serve as an evaluation material for the village government in enhancing the quality of future RKPDes preparation.